2019
DOI: 10.1021/acsami.9b07701
|View full text |Cite
|
Sign up to set email alerts
|

Gate-Tunable and Programmable n-InGaAs/Black Phosphorus Heterojunction Diodes

Abstract: Semiconductor heterostructures have enabled numerous applications in diodes, photodetectors, junction field-effect transistors, and memory devices. Two-dimensional (2D) materials and III–V compound semiconductors are two representative materials providing excellent heterojunction platforms for the fabrication of heterostructure devices. The marriage between these semiconductors with completely different crystal structures may enable a new heterojunction with unprecedented physical properties. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
(119 reference statements)
0
5
0
Order By: Relevance
“…Compared with the traditional bulk materials, 2D materials can exhibit a number of advantages in the field of the artificial synapse including gate-tunability, low-power-switching, , mechanical flexibility, and easy integration . The device structures of 2D material-based artificial synapses can be classified into two-terminal ,, or three-terminal ,,, lateral-, vertical-, and heterojunction- structures. For three-terminal devices, great effort has been devoted into the ferroelectric-gate synaptic transistors, floating-gate synaptic transistors, and electrolyte-gate synaptic transistors .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional bulk materials, 2D materials can exhibit a number of advantages in the field of the artificial synapse including gate-tunability, low-power-switching, , mechanical flexibility, and easy integration . The device structures of 2D material-based artificial synapses can be classified into two-terminal ,, or three-terminal ,,, lateral-, vertical-, and heterojunction- structures. For three-terminal devices, great effort has been devoted into the ferroelectric-gate synaptic transistors, floating-gate synaptic transistors, and electrolyte-gate synaptic transistors .…”
Section: Introductionmentioning
confidence: 99%
“…92 Y. Lee et al have demonstrated an n-InGaAs/BP diode by adopting double-times transfer printing of each NMs onto a SiO 2 /Si substrate via PDMS stamping. 93 This device offers nonvolatile-memory properties through charge trapping in the native phosphorus oxide, exhibiting unique diode characteristics which are gate-controllable and programmable. These multifunctional properties provide numerous potential applications such as novel advanced logic circuits, controllable electric transformers, and neuromorphic devices.…”
Section: Ingaas Nmsmentioning
confidence: 99%
“…remaining three peaks at 161.2, 188.4, and 216.1 cm −1 were attributed to the B 3g and A g vibration modes of SnS (position B1) [26,27] . Similarly, peaks corresponding to the E g and A 1g vibration modes of SnSe 2 (position C2), as well as the , B g , and vibration modes of SnSe (position B2) can be found in the Raman spectrum of the SnSe/SnSe 2 heterostructure (position A2) [19] .…”
Section: Resultsmentioning
confidence: 98%